PEMELIHARAAN DAN PENAMBAHAN DAYA PEMBANGKIT LISTRIK TENAGA SURYA PADA LAHAN PERTANIAN KELOMPOK TANI D’RANGRANG DEPOK (Jurnal AbdiMas Nusa Mandiri, 2025)
The Drangrang farmer group’s agricultural garden, located at RT10 RW03, Tirtajaya Village, Sukmajaya District, Depok, covers an area of approximately 1,500 m². The land is used to cultivate vegetables and crops such as corn, peanuts, and cucumbers. Electricity for agricultural operations is supplied by a Solar Power Plant (PLTS) with an initial capacity of 100 Wp. However, along with land expansion and increased load demand, the existing PLTS system could no longer meet energy needs, requiring a capacity upgrade. This community service activity aimed to provide technical assistance for the installation of additional solar panels to increase the PLTS capacity and fulfill electricity requirements for lighting and water pumps. The method included equipment procurement, system assembly in the garden area, and PLTS testing. The activity was carried out by lecturers and students from the Department of Electrical Engineering, Gunadarma University. The stages consisted of design, installation, testing, and measurement. The upgraded PLTS system now provides 200 Wp, capable of supplying four lighting points and one 160 W water pump. The additional capacity ensures a safer and more continuous power supply, supporting improved agricultural productivity and operational efficiency of the farmer group.
Keywords: Drangrang; PLTS; renewable energy; solar panel; urban farming